Planar Beam Steerable Parasitic Array Antenna System Design Based on the Yagi-Uda Design Method - Seok-Jae Lee; Won-Sang Yoon; Sang-Min Han (International Journal of Antennas and Propagation)
A planar beam steerable array antenna system is proposed with dual-control circuits for feeding and reactive loadings. Two orthogonally arranged planar dipoles are excited by SPDT switching circuits, while the forward and backward beam directions are controlled by the adjusted effective electric lengths of the parasitic dipole elements. The adjusted parasitic dipoles are designed to play the alternative roles of directors and reflectors based on the Yagi-Uda antenna theory. The proposed antenna system with four-way switchable beams has been implemented on a planar substrate and evaluated for orthogonal four-way beam steering performance with good agreement.